Pharmacological inhibition of mitochondrial soluble adenylyl cyclase in astrocytes causes activation of AMP‐activated protein kinase and induces breakdown of glycogen. Issue 12 (11th August 2021) - Jakobsen, Emil; Andersen, Jens V.; Christensen, Sofie K.; Siamka, Olga; Larsen, Martin R.; Waagepetersen, Helle S.; Aldana, Blanca I.; Bak, Lasse K.
Abstract: Mobilization of astrocyte glycogen is key for processes such as synaptic plasticity and memory formation but the link between neuronal activity and glycogen breakdown is not fully known. Activation of cytosolic soluble adenylyl cyclase (sAC) in astrocytes has been suggested to link neuronal depolarization and glycogen breakdown partly based on experiments employing pharmacological inhibition of sAC. However, several studies have revealed that sAC located within mitochondria is a central regulator of respiration and oxidative phosphorylation. Thus, pharmacological sAC inhibition is likely to affect both cytosolic and mitochondrial sAC and if bioenergetic readouts are studied, the observed effects are likely to stem from inhibition of mitochondrial rather than cytosolic sAC. Here, we report that a pharmacologically induced inhibition of sAC activity lowers mitochondrial respiration, induces phosphorylation of the metabolic master switch AMP‐activated protein kinase (AMPK), and decreases glycogen stores in cultured primary murine astrocytes. From these data and our discussion of the literature, mitochondrial sAC emerges as a key regulator of astrocyte bioenergetics. Lastly, we discuss the challenges of investigating the functional and metabolic roles of cytosolic versus mitochondrial sAC in astrocytes employing the currently available pharmacological tool compounds. Main Points: Inhibition of mitochondrial sAC decreases OXPHOS in primary cultured astrocytes. Downstream metabolic effects include activation of AMPK and glycogen degradation.